2021
DOI: 10.1002/1873-3468.14022
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein import dysfunction: mitochondrial disease, neurodegenerative disease and cancer

Abstract: The majority of proteins localised to mitochondria are encoded by the nuclear genome, with approximately 1500 proteins imported into mammalian mitochondria. Dysfunction in this fundamental cellular process is linked to a variety of pathologies including neuropathies, cardiovascular disorders, myopathies, neurodegenerative diseases and cancer, demonstrating the importance of mitochondrial protein import machinery for cellular function. Correct import of proteins into mitochondria requires the co‐ordinated activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 238 publications
(449 reference statements)
1
42
0
1
Order By: Relevance
“…We also found that TOMM40 was upregulated in 14 out of 33 types of cancers (42.4%) ( Supplementary Figure 13B ). Our results are well-correlated with previous reports that TOMM40 (TOM40) and significant numbers of MT protein import machineries overexpressed in cancers such as the TOM complex (TOM20, TOM40, TOM7, and TOM70), TIM23 complex, TIM22 complex, small Tim chaperons and Mia40, and Tim 44 ( 111 , 114 ). To elucidate the functional aspects of TOMM40, we searched the PPI network database in the STRING database ( https://string-db.org/ ).…”
Section: Resultssupporting
confidence: 92%
“…We also found that TOMM40 was upregulated in 14 out of 33 types of cancers (42.4%) ( Supplementary Figure 13B ). Our results are well-correlated with previous reports that TOMM40 (TOM40) and significant numbers of MT protein import machineries overexpressed in cancers such as the TOM complex (TOM20, TOM40, TOM7, and TOM70), TIM23 complex, TIM22 complex, small Tim chaperons and Mia40, and Tim 44 ( 111 , 114 ). To elucidate the functional aspects of TOMM40, we searched the PPI network database in the STRING database ( https://string-db.org/ ).…”
Section: Resultssupporting
confidence: 92%
“…As such, the vast majority of~1200 mitochondrial proteins are nuclear-encoded [3,4]. These proteins are translated via cytosolic ribosomes before being processed and imported into mitochondria through the TIM/TOM system [5]. However, mitochondria also contain a vestigial genome within the matrixin humans, mitochondrial DNA (mtDNA) encodes only 13 polypeptideshighly hydrophobic subunits of the OXPHOS machinery [6].…”
mentioning
confidence: 99%
“…Moreover, ATP6V1A maturations were implicated in the onset of developmental encephalopathy with epilepsy, suggesting its role in regulating neuronal development [65]. A clinical study by Dutta et al [66] reported that two patients with de novo mutations (T607I and I554F) in the C-terminus of the TOM70 protein exhibited white matter abnormalities, hypotonia, hyperreflexia, dystonia, and cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%